2015
DOI: 10.1002/jssc.201401105
|View full text |Cite
|
Sign up to set email alerts
|

Ionic‐liquid‐based dispersive liquid–liquid microextraction combined with high‐performance liquid chromatography for the determination of multiclass pesticide residues in water samples

Abstract: Ionic-liquid-based dispersive liquid-liquid microextraction in combination with high-performance liquid chromatography and diode array detection has been proposed for the simultaneous analysis of four multiclass pesticide residues including carbaryl, methidathion, chlorothalonil, and ametryn from water samples. The major experimental parameters including the type and volume of ionic liquid, sample pH, type, and volume of disperser solvent and cooling time were investigated and optimum conditions were establish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The obtained limit of detection of MBTCA (0.12 pg/m 3 ) is significantly lower than the limits of detection reported by, e.g., Fu et al [6], Zuth et al [31], Ding et al [19], and Kourtchev et al [2] that were 0.005, 1.3, 2, and 4 ng/m 3 respectively. Tadesse et al [12] reported enrichment factors of 10.2–19.6 for DLLME of multiclass pesticide residues in water samples. Additive-assisted DLLME for extraction of polar compounds such as MBTCA provided an enrichment factor of 16.6 that is fairly comparable to earlier DLLME studies of non-polar compounds.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The obtained limit of detection of MBTCA (0.12 pg/m 3 ) is significantly lower than the limits of detection reported by, e.g., Fu et al [6], Zuth et al [31], Ding et al [19], and Kourtchev et al [2] that were 0.005, 1.3, 2, and 4 ng/m 3 respectively. Tadesse et al [12] reported enrichment factors of 10.2–19.6 for DLLME of multiclass pesticide residues in water samples. Additive-assisted DLLME for extraction of polar compounds such as MBTCA provided an enrichment factor of 16.6 that is fairly comparable to earlier DLLME studies of non-polar compounds.…”
Section: Resultsmentioning
confidence: 99%
“…Dispersive liquid–liquid microextraction (DLLME) has gained popularity owing to its simplicity, low cost, enrichment of analyte, and short extraction times [ 8 12 ]. However, traditional sample preconcentration techniques like solid-phase extraction have been used for the extraction of polar compounds from aerosols [ 13 ].…”
Section: Introductionmentioning
confidence: 99%